Penerapan Metode Diskusi Sebagai Upaya Meningkatkan Hasil Belajar Fiqih pada Siswa Madrasah Ibtidaiyah - Muhammad, Devy Habibi; Kurnia, Fitri; Rachmawati, Hani Nafi’ah (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2024)
This article explores efforts to improve the learning achievement of sixth-grade students at MI Islamiyah, Sumberasih District, Probolinggo Regency, by implementing the discussion method in Fiqh lessons. The primary issue identified is that students' learning achievements have not met the Minimum Mastery Criteria (KKM) of 70, which highlights the need for effective teaching strategies. To address this, the study employed Classroom Action Research (CAR), a method designed to improve educational practices through iterative cycles of planning, action, observation, and reflection. The study was conducted in two cycles, with the first cycle showing that 14 students (66.67%) achieved mastery. In the second cycle, the number of students achieving mastery rose to 19 students (90.48%). These results suggest that the discussion method can significantly enhance students' learning outcomes, particularly in subjects such as Fiqh, which require conceptual understanding and critical thinking. Based on these findings, it is recommended that teachers consider incorporating the discussion method into their teaching strategies, especially for subjects that encourage deeper comprehension. The discussion method fosters active participation, critical thinking, and collaborative learning, making it a powerful tool for enhancing student achievement. Teachers should adapt the method to suit the specific content of their lessons and the needs of their students.